Psychometric properties of Sense of Community Scale using Nigerian secondary school students - Ugwuanyi, Christian (Universitas Negeri Padang, 2023)
The populous of Nigeria is fleeing in dread as a result of the obscene security breaches. The school-age teens who may not have a strong feeling of their community are those who are most impacted. Due to the lack of comparable studies in Nigeria, this study carried out the factorial validation of a 36-item SoCS created by Cicognani et al. (2006). The tool was accepted and verified. For this study, a sample of 489 secondary school students was selected using a straightforward random selection procedure. Factor analysis was used to evaluate the validity and reliability of the instrument as part of the factorial validation process. In addition, the exploratory and confirmatory factor analyses were conducted using the principal component matrix with Varimax rotation, and the data model fit was assessed using the root mean square approximation (RMSEA) and confirmatory factor index (CFI). The study's findings revealed that SoCS in the Nigerian setting exhibited good model fit (RMSEA =.041, CFI =.951) and reliability (0.89). The sense of community among teenagers enrolled in school can be measured with the SoCS.